Non-Myeloablative Chemotherapy as Consolidation Strategy After High-Dose Methotrexate-Based Chemoimmunotherapy in Patients With Primary CNS Lymphoma: A Retrospective Single Center Study in China - Sun, Xuefei; Wu, Yuchen; Xing, Ruixian; Bai, Xueyan; Qian, Jun; Zhu, Hong; Cui, Qu; Chen, Yuedan; Liu, Qing; Lai, Wenyuan; Li, Junhong; Wang, Yaming; et al. (Frontiers in Oncology, 2022)
Primary central nervous system lymphoma (PCNSL) remains a disease with poor outcome and high recurrence rate. We retrospectively analyzed the clinical data of 243 immunocompetent patients with PCNSL in Beijing Tiantan Hospital. The median age of PCNSL patients was 57 years (range 10-95 years). For induction therapy, 94.7% of patients received high-dose methotrexate (HD-MTX) containing regimens, and 59.3% received rituximab, which increased over time. The overall response rate was 72.4%, with 58.8% achieving complete response. With a median follow-up of 27.0 months (95% confidence interval 23.6-30.4), the median progression-free survival (PFS) time was 14.0 months (95% CI 9.45-18.55), and the 2-year PFS rate was 33.2%. The median overall survival (OS) was not reached (NR), with an estimated overall survival rate at 4 years of 61.6%. Among 95 patients who completed sequential consolidation chemotherapy with either pemetrexed or etoposide plus cytarabine, the median PFS was 28 months (95% CI 17.11-38.89), and the estimated overall survival at 4 years was 78.7%. In conclusion, HD-MTX based induction chemotherapy with non-myeloablative sequential consolidation chemotherapy is an alternative feasible treatment option.